Surface plasmon-enhanced solution-processed phosphorescent organic light-emitting diodes by incorporating gold nanoparticles. (6th May 2020) - Jou, Jwo-Huei; Lo, Dan; Su, Yu-Ting; Dubey, Deepak Kumar; Kuan, Da-Hsing; Chiang, Chi-Heng; Masim, Frances Camille P; Hatanaka, Koji; Liu, Bei; Subiyanto, Iyan; Liu, Kou-Chen; Nagar, Mangey Ram
Abstract: Organic light-emitting diodes (OLEDs) have attracted increasing attention due to their superiority as high quality displays and energy-saving lighting. However, improving the efficiency of solution-processed devices especially based on blue emitter remains a challenge. Excitation of surface plasmons on metallic nanoparticles has potential for increasing the absorption and emission from optoelectronic devices. We demonstrate here that the incorporation of gold nano particles (GNPs) in the hole injection layer of poly(3, 4-ethylene dioxythiophene):polystyrene sulfonic acid with an appropriate size and doping concentration can greatly enhance the efficiency OLED device especially at higher voltage. Apparently, the spectral of the multiple plasmon resonances of the GNPs and the luminescence of the emitting materials significantly overlap with each other. At 1000 cd m −2 for example, the power efficiency of a studied green device is increased from 29.0 to 36.2 lm W −1, an increment of 24.8%, and the maximum brightness improved from 21 550 to 27 810 cd m −2, an increment of 29.1%, as 2 wt% of a 12 nm GNP is incorporated. Remarkably, designed blue OLED also exhibited an increment of 50% and 35% in power efficacy at 100 and 1000 cd m −2, respectively, for same device structure. The reason why the enhancement is marked may be attributed to a strong absorption of the short-wavelength emission from the device by the gold nano particles, which in turn initiates a strong surface plasmon resonance effect, leading to a high device efficiency.